Suggested high school science activities on industrial pollution and its control - Morales, Manolita Bacolod 1951- (1978)
This study developed and tried out activities based on the study of the waste management strategies employed by selected companies in Cebu. Primary treatment consisted of mechanical devices as screens, bar grills, filter presses and containment booms. Only one company employed a secondary treatment--a combination of an aerobic and oxidation ponds. The activities were tried out by thirty second year students of the high school of St. Joseph's Academy in Cebu. It was concluded in the study that the waste treatment facilities employed by companies are far from satisfactory.
Vita.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Secondary) -- Activity programs -- Philippines -- Cebu City (Cebu); Refuse and refuse disposal -- Study and teaching (Secondary) -- Philippines -- Cebu City (Cebu); Factory and trade waste -- Philippines -- Cebu City (Cebu); Pollution control equipment -- Philippines -- Cebu City (Cebu)